Carbohydrates in Relation to Rooting of Culm Cuttings of Dendrocalamus strictus (Roxb.) - Kumar, Rakesh; Pal, Mohinder (Indian Forester, 2003)
Study was conducted to estimate the carbohydrate content in bamboo culm in relation to its rooting potential. The findings indicate that in Dendrocalamus strictus, the carbohydrate content is not directly related to rooting potential of cuttings. Hence, some other factors may be responsible for initiating the rooting in culm cuttings.